Morphological Organizations in Epitaxial Growth and Removal - Zhang Zhenyu (World Scientific, 1999)
Provides a critical assessment of the current status and the likely future directions of thin-film growth. The text's emphasis is on descriptions of atomic-scale mechanisms controlling the dynamics and thermodynamics of the morphological evolution of the growth front of thin films in diverse systems of fundamental and technological significance. The book covers most of the original and important conceptual developments made in the 1990s. The articles are arranged in five major categories - the theoretical basis, semiconductor-on-semiconductor growth, metal-on-metal growth, metal-on-semiconductor growth, and removal as the inverse process of growth.